A Moderate Interleukin‐6 Reduction, Not a Moderate Weight Reduction, Improves the Serum Iron Status in Diet‐Induced Weight Loss with Fish Oil Supplementation. Issue 20 (26th August 2018) - Huang, Shih‐Yi; Sabrina, Nindy; Chien, Yi‐Wen; Chen, Yi‐Chun; Lin, Shyh‐Hsiang; Chang, Jung‐Su
Abstract : Background & Aims: Whether moderate weight loss or a reduction in IL‐6 improves the serum iron status in overweight (OW) and obese adults supplemented with or without fish oil is explored. Methods and Results: In total, 93 OW/obese Taiwanese adults with ≥2 metabolic components are randomized to a 12‐week calorie‐restricted diet with meal replacement alone (CRMR, n = 45) or supplemented with fish oil (CRMRF, n = 48). Mean reductions in the %body weight and serum IL‐6 are 7.5% versus 5.9% and 21% versus 35% for the CRMR and CRMRF groups, respectively. In the CRMRF group, a moderate loss of IL‐6 (reduced ≥35%) also significantly improves the serum iron and transferrin saturation compared to those with loss of <35% in the mean serum IL‐6 or those of the CRMR group who has a moderate loss of IL‐6 (reduced ≥21%) (all p  < 0.05). In contrast, modest weight loss does not improve the serum iron status. Conclusions: Fish oil is ineffective as an adjunct for weight or fat loss but has beneficial effects on preserving the lean body mass. A significant improvement in the iron status is only observed in those with moderate loss of serum IL‐6 supplemented with fish oil. Abstract : Aaddition of supplemental fish oil in conjunction with a hypocaloric diet for 12 weeks showes no added benefits on body fat or body weight loss, but the addition of n‐3 PUFAs had beneficial effects on preserving the lean body mass and improving the iron status, particularly in those with a moderate IL‐6 reduction.